Identification of Epinastine as CD96/PVR inhibitor for cancer immunotherapy - Xiangrui Zhang; Lihan Zhang; Beibei Li; Qingchao Wang; Peixin Chen; Ranran Shi; Xiuman Zhou; Xiaoshuang Niu; Wenjie Zhai; Yahong Wu; Wenhui Shen; Xiaowen Zhou; et al. (BMC Biology)
Abstract Background Poliovirus receptor (PVR) and its receptor system, including TIGIT, CD226, and CD96, play a pivotal role in orchestrating tumor immune evasion. Upon engagement with PVR on tumor cells, CD96 exerts inhibitory effects on the function of T cells and NK cells, thereby fostering tumor immune evasion. Therefore, screening of immune checkpoint inhibitors (ICIs) targeting the CD96/PVR pathway will provide promising candidates for tumor immunotherapy. Results In this investigation, we employed MOE software to conduct virtual screening of small molecules from the FDA-approved drug library. Our results demonstrated that Epinastine exhibited high affinity for CD96, thereby effectively disrupting the interaction between CD96 and PVR. In vitro co-culture experiments further revealed that Epinastine effectively restored the ability of Jurkat cells to secrete IL-2. In the MC38 tumor-bearing model, Epinastine significantly enhanced the infiltration of T cells and NK cells into the tumor site and augmented their secretion of IFN-γ, leading to effective suppression of tumor growth. Conclusions Our results demonstrated that the development of small molecule inhibitor Epinastine targeting CD96/PVR pathway, which proposed a promising strategy and drug candidate for cancer immunotherapy. Graphical Abstract